New Prenylated Indole Homodimeric and Pteridine Alkaloids from the Marine-Derived Fungus Aspergillus austroafricanus Y32-2 - Peihai Li; Mengqi Zhang; Haonan Li; Rongchun Wang; Hairong Hou; Xiaobin Li; Kechun Liu; Hao Chen (Marine Drugs, 2021)
Chemical investigation of secondary metabolites from the marine-derived fungus Aspergillus austroafricanus Y32-2 resulted in the isolation of two new prenylated indole alkaloid homodimers, di-6-hydroxydeoxybrevianamide E (1) and dinotoamide J (2), one new pteridine alkaloid asperpteridinate A (3), with eleven known compounds (4–14). Their structures were elucidated by various spectroscopic methods including HRESIMS and NMR, while their absolute configurations were determined by ECD calculations. Each compound was evaluated for pro-angiogenic, anti-inflammatory effects in zebrafish models and cytotoxicity for HepG2 human liver carcinoma cells. As a result, compounds 2, 4, 5, 7, 10 exhibited pro-angiogenic activity in a PTK787-induced vascular injury zebrafish model in a dose-dependent manner, compounds 7, 8, 10, 11 displayed anti-inflammatory activity in a CuSO4-induced zebrafish inflammation model, and compound 6 showed significant cytotoxicity against HepG2 cells with an IC50 value of 30 µg/mL.